PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS LINGKUNGAN SEBAGAI SARANA PRAKTIKUM IPA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA DI SMP-IT AR RAHMAH PACITAN - Erviana, Lina (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
This research is motivated by lack of understanding of the concept of eighth grade in Ar Rahmah Pacitan Islamic Integrated Junior High School on science subject. Many learning methods found to improve students performance, but how does the teacher is able to choose the appropriate learning method to gain optimal learning results. The purpose of this research is to increase student’s understanding of concepts. For contextual learning or just rely on the books, sometimes the students feel bored, so the student’s understanding in learning is less and need a help tool. This research uses a classroom action research method, which lasts for two cycles. The chronology of this research, starting from planning, action, observation, and reflection. The subjects are 30 students. Collecting data using tests, practicum, questionnaire, interviews, observation, and documentation. The datas are analyzed by looking at the classical mastery learning students ie 75% of students got a score ≥ 75. The results of this research showed that the media environment based learning can increase student’s understanding of the concept. This is evident from the enhancement in the average results of the first cycle test is 77.8 and the second test is 84.5. The learning model that based on environment succeed in increasing understanding of science concepts with the percentage of completeness initially increased by 48% to 70% in cycle 1 and 93% in cycle 2.